Begonia truncatifolia (Begoniaceae, section Baryandra), a new species from Palawan Island, the Philippines - Bustamante, Rene Alfred Anton; Tandang, Danilo N.; Pranada, Mc Andrew K.; Ang, Yu Pin (Phytotaxa, 2020)
A new species of Begonia sect. Baryandra with 2-locular ovary and cucullate abaxial wing from the town of San Vicente, Palawan is described and illustrated. The new species, B. truncatifolia, is diagnosed against the morphologically similar B. blancii. Both species are endemic to Palawan and are similar in having spathulate leaves, 4-tepaled staminate & pistillate flowers and bilocular ovaries, but B. truncatifolia is significantly different in being comparatively smaller in size (stipules, lamina and inflorescences) and having obtusely rounded to acute lamina apices. The new species is proposed Critically Endangered following the criteria set by the IUCN.